Electro-oculographic abnormalities in amblyopia. Issue 3 (March 1995) - Williams, C; Papakostopoulos, D
Abstract : BACKGROUND--Electrodiagnostic tests have been used to investigate retinal function in amblyopia but previous results have been conflicting. METHODS--It was decided to investigate whether the electro-oculogram (EOG) showed any abnormalities in 12 adult amblyopes and 12 age and sex matched controls with normal vision. The mean amplitudes of the EOG recordings from each eye during 12 minutes of darkness and 18 minutes of light were compared. RESULTS--The mean values from the amblyopic eyes were lower than those from the fellow non-amblyopic eyes. At most time points the difference was significant (p < 0.05). After normalisation of the data to minimise intersubject variation, the reduction in EOG amplitudes of the amblyopic eyes at all time points was significant (p < 0.05). There was no significant difference between the mean values obtained from the right and left control eyes at any time point, either before or after normalisation. CONCLUSIONS--These results provide evidence for a retinal abnormality in amblyopia and implicate the retinal pigment epithelium as being involved. A deficiency in retinal dopaminergic function in amblyopia is proposed as a possible mechanism causing these results.